Peningkatan Proses Belajar Siswa Dengan Model Pembelajaran Make A Match Terhadap Hasil Belajar Pembelajaran Tematik Tema Tematik Tema 2 Subtema Pentingnya Makanan Sehat Bagi Tubuh Kelas V SD Negeri 102010 Liberia - Bina Limbong; Regina Fredika Sipayung (LP3M KH Yazid Karimullah Institute, 2024)
The aim of this research is to increase the level of activity and learning outcomes of students through implementing the make a match learning model. The research method applied is Classroom Action Research (PTK), with the research subject focusing on class V students. Data collection is carried out through tests, observations, and activeness assessment rubrics. Data analysis was carried out descriptively in both quantitative and qualitative aspects. The research results showed a significant increase in student learning activity. In the pre-cycle stage, there were 24 students (64.87%) who were identified as inactive. However, in cycle I, this figure decreased to 9 students (24.32%) who had reached a sufficient level of activeness. In cycle II, student activity increased significantly, reaching 31 students (83.78%) who were classified as active. Meanwhile, for learning outcomes, in the pre-cycle there were 15 students (41%) who achieved completeness. In cycle I, the number of students who completed increased to 20 students (54%), and in cycle II it reached 30 students (81%). Therefore, it can be concluded that through the application of the make a match learning model, there has been a real increase in the activity and learning outcomes of students in this class.